Implementation of the Health Belief Model as a Predictor of Acupuncture Therapy Adherence in Post-Stroke Patients - Efa Yusfi Asrifa; Bhisma Murti; Haryani Saptaningtyas; Hanung Prasetya; Argyo Demartoto; Ika Sumiyarsi Sukamto (Journal of Health Promotion and Behavior, 2025)
Background: Post-stroke symptoms include limb weakness, paralysis, loss of balance, pain and numbness, memory and cognitive disorders, and urinary and digestive problems. The recovery process in post-stroke patients takes a long time, therefore, the patient needs to adhere to acupuncture therapy for recovery. This study aims to analyze the influence of perceived susceptibility, perceived severity, perceived benefits, perceived barriers, self-efficacy, and cues to action on acupuncture therapy adherence in post-stroke patients. Subjects and Method: This study was a cross-sectional study conducted in Yogyakarta, from November to December 2024. A total of 205 patients were selected using random sampling. The dependent variable was adherence to acupuncture therapy in post-stroke patients. Independent variables were perceived vulnerability, perceived severity, perceived benefits, perceived benefits, self-efficacy, and cues to action. The data were analyzed using path analysis. Results: Adherence to acupuncture therapy increased with increased perceived susceptibility (b= 1.19; 95% CI= -0.13 to 2.27; p=0.081), perceived severity (b= 2.16; 95% CI= 0.81 to 3.31; p= 0.001), perceived benefits (b= 1.71; 95% CI= 0.98 to 2.45; p<0.001), self-efficacy (b= 0.73; 95% CI= 0.11 to 1.36; p= 0.022) and cues to action (b= 1.77; 95% CI= 1.08 to 2.45; p<0.001). Conclusion: There is a positive relationship between perceived susceptibility, perceived severity, perceived benefits, self-efficacy, and cues to action on adherence to acupuncture therapy in post-stroke patients. The perceived benefits and self-efficacy are a direct influence on adherence to acupuncture therapy in post-stroke patients, while the perceived susceptibility, perceived severity, and cues to action are indirect influences.